Syriusz : wybor opowiadan - Stryjkowski, Julian (Warszawa : Czytelnik, 1984)
A selection of short stories.
Chiwu -- Ajeleth -- Heinz -- Ruth -- Martwa Fala -- Syriusz -- Na wierzbach ... nasze skrzypce -- Lesny spacer.
Keywords: Short stories, Polish